The Study of the Chemical Synthesis and Preparation of Histone with Post- Translational Modifications - Wang, Zhi-Peng; Wang, Ye-Hai; Chu, Guo-Chao; Shi, Jing; Li, Yi-Ming (Current Organic Synthesis, 2015)
In the post-genomic era, more and more interests have been focusing on epigenetics. The histones studded with certain post-translational modifications (PTMs) are becoming one of the cores in protein chemical biology research. The biological generations and functions of these “histone codes”, such as their structural diversity, sophisticated regulations and complex cross-talks, are gradually discovered but still waiting to be deciphered. However, to prepare enough amount of homogeneously modified histones remain a challenge for chemical biologists. To overcome the shortage of traditional expression, protein total synthesis, semi-synthesis, and unnatural amino acid incorporation are becoming major approaches to fulfill this goal. In this review, we will summarize some typical examples for chemical prepared modified histone proteins for further biological study. The introduction of synthetic chemistry into this realm largely exhibited the importance and potential of chemical tools in biological and biomedical fertile grounds.
Keywords: unnatural amino acid incorporation